Challenges Prospective Teachers Regarding Learning Models in the 4.0 Era (Case Study of PGMI Students) - Sinta Bela Mastura; Puthut Waskito; Amandha Ramadhani (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This study aims to examine the experiences of prospective elementary school teachers with various learning models they witnessed being implemented by teachers during their observations in schools. The research used a descriptive case study method conducted at PGMI UIN Tulungagung. There were 10 respondents in this study. The results showed that all respondents (100%) reported significant experience with the implementation of various learning models by the teachers studied. The following subjects attracted interest and the learning methods applied: First, 37% of participants chose mathematics, with learning methods that included singing, mental arithmetic, media use, and memorization. Second, 26% of participants chose science, with an approach that involved out-of-class practical activities, games, bridges, and media use. Third, 15% of participants chose language subjects, which used methods that combined games and drama. Fourth, for social studies, 12% of participants chose learning methods that included singing and riddles. Another 10% of participants chose religion, which included singing. Approximately 90% of participants indicated that the challenges they noticed in understanding various learning models were how to differentiate between models, methods, approaches, and learning strategies.